1996
DOI: 10.1095/biolreprod54.3.583
|View full text |Cite
|
Sign up to set email alerts
|

Endothelin-1 Stimulates Deoxyribonucleic Acid Synthesis and Contraction in Testicular Peritubular Myoid Cells1

Abstract: In the testis, endothelin-1 (ET-1) is produced by Sertoli cells, and it has been proposed to be a paracrine factor participating in the regulation of tubular and interstitial function. The response of purified testicular peritubular myoid cells (TPMC) to ET-1 was investigated in the present study. TPMC expressed a single class of high-affinity receptors that were shown by competitive binding experiments with sarafotoxin-6c to belong to the ETA subtype. The binding of ET-1 to TPMC was followed by rapid internal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 40 publications
1
21
0
Order By: Relevance
“…Isolated STs were incubated with endothelin-1 for 20 second or 1 min with oxytocin [23]. SEM analysis of the STs showed that only endothelin-1 induced changes in PMC morphology, as previously demonstrated [24] (Fig.…”
Section: Resultsmentioning
confidence: 84%
“…Isolated STs were incubated with endothelin-1 for 20 second or 1 min with oxytocin [23]. SEM analysis of the STs showed that only endothelin-1 induced changes in PMC morphology, as previously demonstrated [24] (Fig.…”
Section: Resultsmentioning
confidence: 84%
“…STF production is Contraction of PTMC is stimulated by endothelin-1 activity. 47,48 Although the precise mechanism for testicular degeneration associated with endothelin receptor antagonists has not yet been elucidated, it is plausible that altered fluid dynamics associated with PTMC impairment may contribute; vascular effects have also been considered. Necrosis of PTMC has been reported following administration of the histamine antagonist cimetidine to rats, with subsequent changes consistent with SC injury.…”
Section: Fluid Disturbancesmentioning
confidence: 99%
“…They can thus be viewed as structural cells bearing also the potential to contract (2,3). A major functional role of these smooth-muscle like cells (myoid cells) in the human species is assumed to be involvement in sperm transport (4).…”
mentioning
confidence: 99%